2007
DOI: 10.1002/polb.21076
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of vulcanized natural rubber by latex state 13C NMR spectroscopy

Abstract: Structural characterization of vulcanized natural rubber was performed by high‐resolution latex‐state 13C NMR spectroscopy. The vulcanized natural rubber latex was prepared by vulcanization of high ammonia natural rubber latex with sulfur and sodium di‐n‐butyldithiocarbamate as vulcanizing agents. High resolution was attained for latex‐state 13C NMR spectroscopy even after vulcanization of the rubber latex, as is evident from no background in spectrum and narrow half width of signals, which were independent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
1
11
2
Order By: Relevance
“…Structure E was observed in the solution-reacted NR sample but not in the solid vulcanized sample. Structure F was part of structure ε, and its presence was predicted but not identified experimentally in previous studies. , As discussed above, the crosslinked structure ε containing a vinylidene group was identified in this work for the first time. Furthermore, the presence of cyclic structure G could not be confirmed using our data.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Structure E was observed in the solution-reacted NR sample but not in the solid vulcanized sample. Structure F was part of structure ε, and its presence was predicted but not identified experimentally in previous studies. , As discussed above, the crosslinked structure ε containing a vinylidene group was identified in this work for the first time. Furthermore, the presence of cyclic structure G could not be confirmed using our data.…”
Section: Resultsmentioning
confidence: 54%
“…These studies reported the presence of carbon signals of possible crosslinking points in structures A−C, H, and I 47 (Figure 2a) and predicted the crosslinked structures D−F. 42,43 However, many questions remain. First, unlike commercial NR products, the samples used in the above studies were prepared without the kneading or heat pressing stages commonly used for preparing NR products (see Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the UV-irradiated PVNRL and the NR latex were only characterized using 13 C nuclear magnetic resonance spectroscopy (Bruker Biospin 500 13 C NMR operating at 500 MHz). The samples for 13 C NMR were prepared and measured at 25 °C …”
Section: Methodsmentioning
confidence: 99%
“…As these do not appear in the solution 13 C-NMR spectrum of uncured natural rubber, they must be derived from crosslinks. Past studies yielded single broad signals at 40, 44, 50 and 58 ppm, respectively, each of which was treated as a single signal for assignment and analysis [12,13,[22][23][24][25][26][34][35][36][37][38]. However, using an FG-MAS probe, fast MAS and NMR locking, it was shown that a plurality of sharp signals existed at 40, 44, 50 and 58 ppm, broad signals disappearing completely from the spectrum.…”
Section: One-dimensional Nmr Measurementsmentioning
confidence: 99%